Lipidomic Impacts of an Obesogenic Diet Upon Lewis Lung Carcinoma in Mice - Sundaram, Sneha; Žáček, Petr; Bukowski, Michael R.; Mehus, Aaron A.; Yan, Lin; Picklo, Matthew J. (Frontiers in Oncology, 2018)
Metabolic reprogramming of lipid metabolism is a hallmark of cancer. Consumption of a high-fat obesogenic diet enhances spontaneous metastasis using a Lewis lung carcinoma (LLC) model. In order to gain further insight into the mechanisms by which dietary fats impact cancer progression, we conducted a lipidomic analysis of primary tumors originated from LLC from mice fed a standard AIN93G diet or a soybean oil-based high-fat diet (HFD). Hierarchical clustering heatmap analysis of phosphatidylcholine (PC) lipids and phosphatidylethanolamine (PE) lipids demonstrated an increase in polyunsaturated fatty acids (PUFA)-containing phospholipids and a decrease in mono-unsaturated fatty acids (MUFA)-containing lipids in tumors from mice fed the HFD. The quantities of 51 PC and 24 PE lipids differed in LLC tumors derived from mice fed the control diet and the HFD. Analysis of triacylglycerol (TAG) lipids identified differences in 32 TAG (by brutto structure) between the two groups; TAG analysis by neutral loss identified 46 PUFA-containing TAG species that were higher in mice fed the HFD than in the controls. Intake of the HFD did not alter the expression of the de novo lipogenesis enzymes (fatty acid synthase, acetyl-CoA carboxylase-1, stearoyl-CoA desaturase-1). Our results demonstrate that the dietary fatty acid composition of a HFD is reflected in the higher order lipidomic composition of primary tumors. Subsequent data are needed to investigate how these lipidomic changes may be used for targeted dietary intervention to reduce tumor growth and malignant progression.